The princess and the pirate - Goldwyn, Samuel, 1926-; Butler, David, 1894-1979.; Hope, Bob, 1903-2003; Mayo, Virginia, 1920-2005; Slezak, Walter, 1902-1983; Brennan, Walter, 1894-1974.; McLaglen, Victor, 1886-1959.; MGM Home Entertainment Inc. (Santa Monica, CA : Metro Goldwyn Mayer Home Entertainment, 2005)
A 17th century entertainer exiled from England and shipped to America falls in love with a princess who is kidnapped by pirates.
Title from container.
Originally released as a motion picture in 1944.
Suggested by a story by Sy Bartlett.
Bob Hope, Virginia Mayo, Walter Slezak, Walter Brennan, Victor McLaglen.
MPAA rating: Not rated.
DVD, region 1, full screen presentation; Dolby Digital mono.
Keywords: Man-woman relationships -- Drama; Entertainers -- Drama; Princesses -- Drama; Feature films; Video recordings for the hearing impaired; French language materials; Spanish language materials